The development of an inventory to determine the practice of the Lasallian values by high school graduates of La Salle Schools - Peralta, Siegfredo M., FSC (Animo Repository, 1991)
The purpose of this thesis was to identify and validate an inventory that determines the practice of Lasallian values by secondary school students of La Salle Schools. Specifically, the study was designed to: (1) Search for the content domain of Lasallian values (2) Identify indicators to assess Lasallian values (3) Test the inventory for content validity and internal consistency of the indicators. The findings showed that seven domains subjected to content validation by experts were accepted as indicators for a Lasallian high school graduate. The seven content domains were: personality, social concern, work attitude or work, Christian, La Sallite, academic achiever and academics. Furthermore, an instrument that measures the practice of Lasallian values among high school graduates was developed. The 46 item inventory was statistically validated through factor and item analysis. All seven content domains were covered by the 46 items. The proposed recommendations are: 1) All Lasallian high schools in the Philippines administer the instrument at the beginning and at the end of the school year to measure the extent of practice of Lasallian values by its students. 2) The scores be transformed into percentiles in order to assess the performance of the student, since norms have not been established. 3) Test results be compiled and forwarded to the researcher so that norms for all Lasallian high school graduates of the Philippines can be established. 4) A study to measure the practice of Lasallian values among students from La Salle elementary schools be done since there already exist one for the college.